The Effect of E-Learning Learning Model on Student Motivation - Febi Yuandini; Sarkadi Sarkadi; Nurzengky Ibrahim (Universitas Sebelas Maret, 2020)
Learning is a process of interaction between teachers and students and the elements in them. The teacher is the most dominant factor that determines the quality of learning. Education is the first step for someone to know something, both himself, the surrounding environment and when interacting with others, with education, a person can become a human who is trained and has skills in life. Especially during this pandemic, which is a widespread effect of the influence of Covid-19, so that distance learning is something that should be done, as a preventive measure from the dangers of the disease. The purpose of this study was to determine whether the E- Learning learning model can affect student learning motivation. The population and sample in this study were students at Islamic Village Senior High School 2020/2021 academic year. The method used in this research is descriptive quantitative with One-shot case study. Data analysis by calculating the correlation coefficient and its significant test, which is then followed by determining the regression equation. The results of this study indicate that the E-Learning learning model influences student learning motivation.